From farm to fork: it could be the case of Lactic Acid Bacteria in the stimulation of folates biofortification in food crops. (August 2020) - Viscardi, Sharon; Marileo, Luis; Barra, Patricio Javier; Durán, Paola; Inostroza-Blancheteau, Claudio
Graphical abstract: Highlights: B-group vitamins, essential and critical micronutrients for human diet, are easily destroyed during cooking. Natural folate form produced by certain bacteria, would be more efficient and secure alternative than the folic acid supplemented in enriched foods. Lactic acid bacteria could be employed as plant probiotic in order to accumulate B-group vitamins in vegetable and fruits for human nutrition. Abstract : B-group vitamins are essential nutrients for living organisms. Despite that B-group vitamins are present in a multiplicity of foods, vitamin deficiency in human still occur in many countries, mainly by inadequate food intake and unbalanced diets. To overcome this global health problem, chemistry food supplementation is a widely used alternative. Moreover, in the specific case of folic acid, the biofortification with the natural folate form 5-methyltetrahydrofolate (5-MTHF), found in vegetables and produced by certain bacterial taxa such is the case of Lactic Acid Bacteria (LAB), would be a more efficient and secure alternative than the food supplementation of foods with folic acid. This review recommends the possibility to use LAB as an economically sustainable and environmentally friendly plant probiotic in order to produce vitamins biofortificated crops. This new approach could lead something interesting in two aspects: on one hand, the promotion of plant growth, and on the other hand, a biofortificated food crop for human nutrition and health safety to food security.